Errance, appartenance, reconnaissance dans la musique savante occidentale - El-Ghadban, Yara (Université de Montréal, 2008)

Facing the Music: Rituals of Belonging and Recognition in Contemporary Western Art Music - El-Ghadban, Yara (American Ethnologist, 2009)
In this article, I examine the tense relationship between belonging and recognition that occurs as two young composers try to situate their musical identities between the urge to contest the hegemony of Western art music and the desire to be part of and recognized within this musical tradition. I draw on their participation as finalists in an international composition competition to examine how issues of identity, postcoloniality, and belonging, on the one hand, and of musical authorship, subjectivity, and agency, on the other hand, are woven into the highly ritualized processes of evaluation and recognition in contemporary Western art music.